2008
DOI: 10.1038/nature07345
|View full text |Cite
|
Sign up to set email alerts
|

SAP-controlled T–B cell interactions underlie germinal centre formation

Abstract: Generation of long-term antibody-mediated immunity depends on the germinal centre (GC) reaction, which requires cooperation between antigen-specific T and B lymphocytes. In the human X-linked lymphoproliferative disease and its gene-targeted mouse model, loss-of-function mutations in signalling lymphocyte activation molecule-associated protein (SAP, encoded by SH2D1a) cause a profound defect in GC formation by an as yet unknown mechanism. Using two-photon intravital imaging, here we show that SAP deficiency se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
684
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 549 publications
(726 citation statements)
references
References 45 publications
38
684
1
3
Order By: Relevance
“…Recent studies have also suggested the requirement of stable DC:T cell interactions for the induction of immunity, rather than tolerance (15,(20)(21)(22). Strikingly, recent publications suggest that peptide:class II complexes that persist for long periods of time may be an essential feature of a germinal center reaction (23,24). All these studies are consistent with the possibility that peptides that have long-lived interactions with class II may have a selective advantage during competitive CD4 T cell priming in vivo.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Recent studies have also suggested the requirement of stable DC:T cell interactions for the induction of immunity, rather than tolerance (15,(20)(21)(22). Strikingly, recent publications suggest that peptide:class II complexes that persist for long periods of time may be an essential feature of a germinal center reaction (23,24). All these studies are consistent with the possibility that peptides that have long-lived interactions with class II may have a selective advantage during competitive CD4 T cell priming in vivo.…”
supporting
confidence: 74%
“…1A). Strikingly, however, when the expansion of HEL [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]-specific T cells was monitored after coadministration with several high-stability dominant peptides, there was a dramatic loss in the number of T cells detected. To verify this important finding, a peptide from OVA, for which several peptide variants of altered kinetic stabilities with class II have been defined (1) and known priming doses so they are loaded at similar initial epitope densities (Fig.…”
Section: Peptides With Fast Off-rates From Class II Elicit Diminishedmentioning
confidence: 99%
See 1 more Smart Citation
“…Most GC Tfh cells have a CXCR5 hi , CCR7 lo , PSGL‐1 lo , programmed cell death protein 1 (PD‐1) hi phenotype and express high levels of Bcl6, Maf, and SLAM‐associated protein (SAP). SAP expression is essential for GC formation,135 preventing inhibitory signaling through SLAM family member 6 (SLAMF6) to enable Tfh‐B cell adhesion,136 which is crucial for Tfh cell retention in GCs and provision of help to B cells. Bcl6 plays a central role in Tfh cell differentiation,115, 137, 138 but other transcription factors that act upstream and downstream of Bcl6 are also required (reviewed in 139).…”
Section: T Follicular Helper Cells and Their Role In Bnab Inductionmentioning
confidence: 99%
“…The first step towards GC formation is activation of naïve B cells by exogenous T-cell dependent antigen in the follicles of peripheral lymphoid tissues. Next, antigen-engaged B-cells migrate to the border between the follicles and the T cell zone or interfollicular zones, where they undergo proliferation and interact with cognate Tfh cells within 1-3 days after stimulation [18][19][20][21]. B-cells can then differentiate into extrafollicular plasma cells and leave the follicle to generate low-affinity antibodies, or alternatively can enter the GC pathway [22].…”
Section: Gc B Cell Development and B Cell Lymphomagenesismentioning
confidence: 99%